MCDM-AHP Method in Decision Makings - Nor Fillianie, Aziz; Sorooshian, Shahryar; Fatimah, Mahmud (Asian Research Publishing Network (ARPN), 2016)

(untitled)
Analytic Hierarchy Process (AHP) is among the most popular methods of decision-makings. This article contains the tutorial document composed of a short discussion on AHP presented at the International conference on “Proceedings of Engineering Technology International Conference”. The conference would be held at Bali, Indonesia during August 10-11, 2015. The paper starts with the short review of Multi-criteria Decision Making and AHP. Then it discusses about the techniques and formulae that are used in the AHP decision-making method. Lastly, this paper recommends AHP to future researchers and professionals with highlights of the reasons to use the methodology process when engaged in complex decision-making problems.